Repurposing the repurposed: thalidomide analogs as immune stimulants to overcome T cell exhaustion. Issue 8 (18th August 2022) - Słabicki, Mikołaj; Sperling, Adam S.
Abstract : In this issue of Cell Chemical Biology, Geng and colleagues employ a novel mouse model of humanized cereblon (Crbn) to provide insights into the immunomodulatory effects of lenalidomide and provide rationale for potential therapeutic combinations including anti-PD1 immunotherapy. Abstract : In this issue of Cell Chemical Biology, Geng and colleagues employ a novel mouse model of humanized cereblon (Crbn) to provide insights into the immunomodulatory effects of lenalidomide and provide rationale for potential therapeutic combinations including anti-PD1 immunotherapy.